Proceedings of the 3rd Symposium on Usable Privacy and Security 2007
DOI: 10.1145/1280680.1280686
|View full text |Cite
|
Sign up to set email alerts
|

Tracking website data-collection and privacy practices with the iWatch web crawler

Abstract: In this paper we introduce the iWatch web crawler, a tool designed to catalogue and analyze online data practices and the use of privacy related indicators and technologies. Our goal in developing iWatch was to make possible a new type of analysis of trends, the impact of legislation on practices, and geographic and social differences online. In this paper we present preliminary findings from two sets of data collected 15 months apart and analyzed with this tool. Our combined samples included more than 240,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Basic statistics indicate that our results are in line with previous, similar endeavors [7] [8]. We omit them for brevity's sake.…”
Section: IIsupporting
confidence: 88%
“…Basic statistics indicate that our results are in line with previous, similar endeavors [7] [8]. We omit them for brevity's sake.…”
Section: IIsupporting
confidence: 88%
“…They also proposed a categorization technique using a DNS SOA record we adopt in our system. Carlos et al [6] reported measurement results of WebCrawler. They crawled 15 months worth of data and obtained 240,000 pages from over 24,000 domains across 47 countries.…”
Section: Measurementsmentioning
confidence: 99%
“…Jensen, et al [17] developed a web crawler that hunted for the presence of trackers and other user tracking mechanisms. Others have studied the prevalence and mechanisms by which user information can be collected [20].…”
Section: B Related Workmentioning
confidence: 99%
“…Beyond simply analytics, advertising networks have been expanding their capabilities with the goal of most efficiently presenting effective ads to users [17], [20]. These advancements have come in many forms, from context aware advertising to the building of user profiles to deliver custom ad experiences [11].…”
Section: Introductionmentioning
confidence: 99%